2015
DOI: 10.1080/00380768.2015.1005540
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silicon on alleviation of salt stress in borage (Borago officinalisL.)

Abstract: The effects of exogenous silicon (Si) on salt (NaCl)-stressed borage (Borago officinalis L.) plants were investigated in this study. Six levels of Si (0, 0.5, 1, 1.5, 2, 2.5 mM) and two levels of NaCl (0 and 120 mM) were applied to study the effect of NaCl and Si on some physiological, biochemical and anatomical properties of Borago officinalis L. Salt stress reduced fresh and dry weight, protein contents and catalase activity. In contrast, proline, glycine betaine, malondialdehyde and activity of superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Therefore, ROS scavenging is most important defense mechanism to cope with stress condition in plants (Sharma et al, 2012; Baxter et al, 2014; Das and Roychoudhury, 2014). According to previous reports, exogenously Si can improve the ability of ROS scavenging by regulation of antioxidants enzyme activity (Torabi et al, 2015; Kim et al, 2016; Tripathi et al, 2017). Furthermore, regulation pattern across various crop plants is different depending upon the exposure time of the stress (Sharma et al, 2012; Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, ROS scavenging is most important defense mechanism to cope with stress condition in plants (Sharma et al, 2012; Baxter et al, 2014; Das and Roychoudhury, 2014). According to previous reports, exogenously Si can improve the ability of ROS scavenging by regulation of antioxidants enzyme activity (Torabi et al, 2015; Kim et al, 2016; Tripathi et al, 2017). Furthermore, regulation pattern across various crop plants is different depending upon the exposure time of the stress (Sharma et al, 2012; Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
“…According to Kim et al (2014c), the application of Si in rice plants under salinity significantly decreased the activities of non-enzymatic MDA and enzymatic antioxidants POD, PPO, and CAT on the other hands, Torabi et al (2015) observed that when they applied Si to borage plant, SOD activity was significantly increased in Si treatment but activity of CAT and APX was slightly decreased in Si application (Table 1). However, Shekari et al (in press) found that activities of CAT, APX, SOD, and POD were highly increased under Si application with NaCl to herbal Anethum graveolens plants.…”
Section: Salinity Stressmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding the synthesis of antioxidants, Kim and collaborators in 2017 [66] made an extensive compendium of the effects of Si on antioxidant metabolism, evidencing that there is more information related to the increase of enzymatic antioxidants such as SOD, CAT, and APX in plants subjected to a variety of abiotic stresses such as heavy metal toxicity [44,67], salinity [68,69], and UV radiation [70], among others.…”
Section: Proposed Mechanisms Of Action Of Iodine Selenium and Silicmentioning
confidence: 99%
“…Zhang et al (2019) reported that application of biochar into soil could significantly improve the physicochemical properties of the soil under salt stress and greatly decrease exchangeable Na + and Cl − contents in the soil, proving a better soil environment for rice seedlings under salt stress. Additionally, the application of nitrogen and silicon could alleviate the adverse effects of salt stress and adjust the plants to perform normally by detoxifying the ROS (Siddiqui et al, 2010;Torabi et al, 2015). Athar et al (2008) reported that exogenously applied ascorbic acid alleviated the salt stress in wheat via improving photosynthetic capacity of wheat against salt-induced oxidative stress and maintaining ion homeostasis.…”
Section: Introductionmentioning
confidence: 99%